Strengthening Rice Farmers' Social Capital in Increasing Agricultural Productivity - Ambo Upe; Mohamad To’at; Shingirai Stanley Mugambiwa; Hertly Huma; Ahmed Samad Akenbi (CV. Literasi Indonesia, 2021)
This study aims to determine the pattern of strengthening social capital in increasing agricultural productivity in Tridana Mulya Village. The approach used in this study is a qualitative approach with data collection techniques including interviews, observation, and documentation. In this study, 19 rice farmers were used as informants. The results showed that the strategy of strengthening the social capital of rice farmers in increasing agricultural productivity in Tridhana Mulya Village included mutual trust and cooperation. The mutual trust of rice farmers in Tridhana Mulya Village is in the form of providing agricultural business capital, increasing the work ethic of rice farmers, increasing farmers' tenacity in farming, and allocation of working hours by farmers. While strengthening social capital through cooperation, namely cooperation in maintaining facilities and infrastructure, cooperation in working on rice fields and the use of livestock manure for fertilizer, cooperation in maintaining agricultural hygiene, and cooperation in maintaining the cleanliness of agricultural irrigation.